Transformações geométricas: fazendo arte na aula de matemática - Sanches, Aparecida de Souza Costa (Universidade Federal de São Carlos, 2021)
The present work aims to analyze the study of symmetry in Elementary School, through classes given online, aiming at the active participation of the student in the teaching and learning process of Mathematics, using computational resources to establish a significant relationship between the school contents in the area of Geometry and works of art. To verify the learning, sheets of pedagogical activities were prepared, which could be printed or copied, for the students to solve. The elaborated activity sheets explored and used the concepts of symmetry in order to assist in learning and visualizing these contents. The activities were applied online, through the Google Meet, WhatsApp and Classroom applications in a public school in Minas Gerais, in an eighth grade class, seeking student-student and student-teacher interaction for conducting and carrying out the activities proposed in class. We can say that the virtual class made it possible to improve the teaching of symmetry and, also, that the dialogues with the students contributed to the learning of the contents covered in class.
Geometric transformations: making art in math class
Keywords: Geometria; Simetria; Arte; Geometry; Symmetry; Art; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM